APLIKASI DAERAH RAWAN PENYAKIT MENGGUNAKAN ALGORITMA COMPLETE LINKAGE CLUSTERING - Uun Amalia Ramadhani; Natalis Ransi; Jumadil Nangi (Informatics Engineering Department of Halu Oleo University, 2019)
Kendari City Health Office is a group that has one task to control the spread of a certain particular disease. To carry out its duties and functions, ideally, the Health Office must have the ability to divide areas that are vulnerable and not prone to disease. To facilitate the dividing, this study was made which aims to build an application that is implemented using the complete-linkage clustering method by forming clusters of data on the number of cases of the disease in 10 sub-districts in Kendari City in 2012 to 2016. Identified diseases are DHF, Diarrhea, and TB. Algorithm Complete Linkage Clustering is a group analysis method that attempts to build a hierarchy of data groups, grouping data with two or more objects that have the closest similarity, then proceed to another object that has a second closeness. The results showed that the areas prone to DHF were Kadia and Wua-Wua sub-districts with an index value of 47.80. Areas that are prone to Diarrhea disease are Puuwatu sub-district with an index value of 1181.40, area which is susceptible to TB disease is West Kendari sub-district with an index value of 92.40. The system can group and map disease-prone areas in the city of Kendari, using Complete Linkage Clustering.Keywords—Complete-Linkage Clustering, Health Service, Dengue Fever, Diarrhea, Tuberculosis (TBC) DOI : 10.5281/zenodo.3183951